Synthesis and pharmacological evaluation of novel naphthoquinone derivatives containing 1,2,4-triazine and 1,2,4-triazole moieties - Polish, N. V.; Nesterkina, M. V.; Protunkevych, M. S.; Karkhut, A. I.; Marintsova, N. G.; Polovkovych, S. V.; Kravchenko, I. A.; Voskoboinik, O. Y.; Kovalenko, S. I.; Karpenko, O. V.; Поліш, H. В.; Нестеркіна, М. В.; et al. (My University, 2021)
Novel naphthoquinone derivatives bearing 1,2,4-triazine- (4a–b) and 1,2,4-triazole (5a– e) pharmacophores have been synthesized; their structure was confirmed by electrospray ionization mass spectrometry, 1H NMR, 13C NMR, IR spectroscopies and elemental analysis. The obtained heterocyclic compounds were estimated for their anticonvulsant activity on models of chemical- and electrical-induced seizures in pentylenetetrazole (PTZ) and maximal electroshock (MES) tests, respectively. Forced swimming test was used to evaluate the antidepressant effect of the naphthoquinone derivatives under study. Compounds 4a–b and 5a–e (100 mg kg–1) demonstrated anticonvulsant action comparable with valproic acid in PTZ-test and prevented the death of 100% of mice in MES model at 3 h and 24 h after oral administration. Moreover, these derivatives showed prolonged antidepressantlike properties, significantly reducing the duration of immobility time in comparison with the reference drug amitriptyline. Синтезовано нові похідні нафтохінону, що містять фармакофорні фрагменти 1,2,4-триазину (4a-b) та 1,2,4-триазолу (5a-e) з подальшим підтвердженням їх структури за допомогою ESI-MS, 'Н-ЯМР, 13С-ЯМР, ІЧ та елементного аналізу. Одержані гетероциклічні сполуки оцінювали за їх антиконвульсантною активністю на моделях хімічних та електричних судом у тесті пентилентетразолу (PTZ) та максимального електрошоку (MES). Тест на примусове плавання (FST) був використаний для оцінки антидепресивного ефекту досліджуваних похідних нафтохінону. Сполуки 4a-b та 5a-e (100 мг/кг) продемонстрували протисудомну дію, порівнянну з вальпроєвою кислотою в PTZ-тесті, і запобігли загибелі 100% мишей на моделі MES через 3 год та 24 год після перорального прийому. Більше того, ці похідні показали тривалу дію, подібну антидепресантам, значно зменшували тривалість часу нерухомості порівняно з референтним препаратом амітриптиліном.
Синтез та фармакологічне оцінювання нових похідних нафтохінону, що містять фрагменти 1,2,4-триазину та 1,2,4 триазолу
Keywords: naphthoquinone derivatives; 1,2,4-triazine; 1,2,4-triazole; technology; anticonvulsant; antidepressant; похідні нафтохінону; 1,2,4-триазин; 1,2,4-триазол; технологія; протисудомний засіб; антидепресант